Vides i successos de quatre monjos de Sant Jeroni de Cotalba. - GALERA, RUBÉN (Scripta, 2020)
The monastery of Sant Jeroni de Cotalba is one of the great works that the duke of Gandia, Alfons el Vell, carried out in the xiv century. Although it was founded by twelve monks brought from the Plana de Xàbia, gradually they increased the number of religious that it could host, in order to arrive at forty. One of those monks, who was an archivist, took care of leaving in writing most memorable ephemerides of the vicissitudes of the monastery and of their monks. Over time, that served for the historians of the Order, as José Sigüenza, to require every monastery the most relevant data of the foundation and the benefactors, but above all the exemplary lives of the monks. Luckily, Francesc del Castillo, accoutant and archivist of Cotalba in the middle of the 18th century, had enough information to write his Historia del Real Monasterio de Sant Jerónimo de Gandía o de Cotalva. The objective of this article is so to make known only the exceptional lives of the monks of Cotalba who, within the monastic life, they witnessed beyond the grave events, healed the chronic ill by faith and preached for weeks with very few hours of rest.